Communication-based on local wisdom as a fortress of family resilience in the era of globalization: Experiences from Javanese speech culture - Muhammad Muhajir (Islamic Communication Journal, 2022)
This study discusses the urgency of communication in a family relationship. The author makes use of communication-based on Javanese local wisdom as an effort to build family resilience in the era of globalization. The method used is descriptive-analytic in explaining the communication based on Javanese local wisdom in the family is realized to build family resilience in the era of globalization. The results of this study show that the local wisdom of Java; 1) "ana catur mungkur," 2) "yen ana rembug dirembug, nanging olehe ngrembug kanthi ati sing sareh," and 3) "aja tumindak grusa-grusu, nanging tumindak kanthi landesan pikiran kang wening," is a local Wisdom of Java that has philosophical, cultural, and moral values that can be used for effective communication as an effort to build family resilience. The three local wisdom of Java can be realized openness, mutual care, and mutual protection. These attitudes make communication within a family better. If the communication pattern is well-realized, the family resilience will be better according to the function and purpose of the family itself.***Tulisan ini fokus membahas tentang urgensi komunikasi dalam sebuah hubungan keluarga. Penulis menggunakan komunikasi berbasis kearifan lokal Jawa sebagai upaya membentuk ketahanan keluarga di era globalisasi. Studi ini merupakan kajian kepustakaan (library research) dengan metode deskriptif-analitik dalam menjelaskan bagaimana komunikasi berbasis kearifal lokal Jawa dalam keluarga dapat digunakan sebagai upaya membentuk ketahanan keluarga di era globalisasi. Hasil studi menunjukkan bahwa kearifan lokal berupa tutur Jawa; 1) “ana catur mungkur,” 2) “yen ana rembug dirembug, nanging olehe ngrembug kanthi ati sing sareh,” dan 3) “aja tumindak grusa-grusu, nanging tumindak kanthi landesan pikiran kang wening,” merupakan kearifan lokal Jawa yang mempunyai nilai-nilai filosofis, budaya, dan moral yang dapat digunakan untuk komunikasi yang efektif sebagai benteng ketahanan keluarga. Ketiga kearifan lokal Jawa tersebut mewujudkan sikap keterbukaan, saling memahami, dan saling menjaga. Sikap-sikap tersebut menjadikan komunikasi dalam sebuah keluarga lebih baik. Jika pola komunikasi telah terwujud dengan baik, maka ketahanan keluarga pun akan semakin baik sesuai fungsi dan tujuan keluarga itu sendiri.